Oxidation of Phenol by Two Tetraazamacrocyclic Cu(II) Complexes Catalysts - Bi, Jian-Hong; Yao, Fu-Hou; Hu, Nai-Liang (Asian Journal of Chemistry, 2011)
The catalytic oxidation of phenol to hydroquinone and catechol was performed in the presence of the two tetraazamacrocyclic copper(II) complexes of CuL1(ClO4)2 and CuL2(ClO4)2 using H2O2 as oxidant and DMF as solvent. When the CuL1(ClO4)2 and CuL2(ClO4)2 were used as catalysts, 31.4 % phenol conversion was obtained with 48.1 % selectivity to diphenol and 29.9 % phenol conversion was obtained with 43.4 % selectivity to diphenol in the optimal reaction conditions.